Lung-homing nanoliposomes for early intervention in NETosis and inflammation during acute lung injury - Jungbum Kim; Donghyuk Seo; So-Yeol Yoo; Hye-Jin Lee; Jisun Kim; Ji Eun Yeom; Jae-Young Lee; Wooram Park; Kyung Soo Hong; Wonhwa Lee (Nano Convergence)
Abstract Acute lung injury (ALI) is characterized by severe inflammation in lung tissue, excessive immune response and impaired lung function. In hospitalized high-risk patients and cases of secondary infection due to surgical contamination, it can lead to higher mortality rates and require immediate intervention. Currently, clinical treatments are limited in symptomatic therapy as mechanical ventilation and corticosteroids, having insufficient efficacy in mitigating the cause of progression to severe illness. Here we report a pulmonary targeting lung-homing nanoliposome (LHN) designed to attenuate excessive Neutrophil Extracellular Trap formation (NETosis) through sivelestat and DNase-1, coupled with an anti-inflammatory effect mediated by 25-hydroxycholesterol (25-HC), offering a promising intervention for the acute phase of ALI. Through intratracheal delivery, we intend prompt and constant action within the lungs to effectively prevent excessive NETosis. Isolated neutrophils from blood samples of severe ARDS patients demonstrated significant anti-NETosis effects, as well as reduced proinflammatory cytokine secretion. Furthermore, in a murine model of LPS-induced ALI, we confirmed improvements in lung histopathology, and early respiratory function. Also, attenuation of systemic inflammatory response syndrome (SIRS), with notable reductions in NETosis and neutrophil trafficking was investigated. This presents a targeted therapeutic approach that can be applied in early stages of high-risk patients to prevent severe pulmonary disease progression.